Graphdiyne-based flexible respiration sensors for monitoring human health. (August 2021) - Li, Yuan; Zhang, Mingjia; Hu, Xiuli; Yu, Lingmin; Fan, Xinhui; Huang, Changshui; Li, Yuliang
Highlights: Respiration sensors with ultra-sensitive characteristics can monitor the various status of human breath in real-time. Non-contact monitoring distance of more than 40 cm can be realized. The respiration sensor can easily monitor the instantaneous changes in humidity caused by skin vapor. DTF calculation reveals the unique response mechanism of GDY. Printing strategy constructs breathing sensors to promote GDY's large area application. Graphical Abstract: ga1 Abstract: Monitoring respiration is a pivotal way to sense the health of the human body and deal with respiratory diseases. Here, we utilize the porous graphdiyne (GDY) material to construct printed respiration sensors suitable for life and health monitoring. These sensors exhibit ultrasensitive responses and rapid recovery performance under real-time respiratory conditions, realizing non-contact detection with a long distance of 40 cm. Even the instantaneous change of weak fingertip moisture can also be easily monitored by such respiratory sensors. Synchronous density functional theory calculations reveal the critical role of GDY's unique acetylene structure on the easy adsorption/desorption of water molecules, which results in enhanced conductivity during the entire sensing process. These results provide a new carbon-based material as ink to print ultrasensitive respiration sensors, which can be used to develop large-scale industrialized integrated smart breathing masks or skin monitors, significantly expanding the prospects of carbon materials in multifunctional electronic skin.